A novel, homozygous nonsense variant of the CDHR1 gene in a Chinese family causes autosomal recessive retinal dystrophy by NGS‐based genetic diagnosis. Issue 11 (30th August 2018) - Fu, Jiewen; Ma, Lu; Cheng, Jingliang; Yang, Lisha; Wei, Chunli; Fu, Shangyi; Lv, Hongbin; Chen, Rui; Fu, Junjiang
Abstract: Retinal dystrophy is an inherited, heterogeneous, chronic and progressive disorder of visual functions. The mutations of patients with autosomal recessive retinal retinopathy cone‐and‐rod dysfunction and macular dystrophy have not been well described in the Chinese population. In this study, a three‐generation Chinese retinal dystrophy family was recruited. Ophthalmic examinations were performed. Targeted next generation sequencing (TGS) was used to identify causative genes, and Sanger sequencing was conducted to verify candidate mutations and co‐segregation. Reverse transcription (RT)‐PCR was applied to investigate the spatial and temporal expression patterns of cdhr1 gene in mouse. A novel, homozygous, deleterious and nonsense variant (c.T1641A; p.Y547*) in the CDHR1 gene was identified in the family with autosomal recessive retinal dystrophy, which was co‐segregated with the clinical phenotypes in this family. RT‐PCR analysis revealed that cdhr1 is ubiquitously expressed in eye, particularly very high expression in retina; high expression in lens, sclera, and cornea; and high expression in brain. In conclusion, our study is the first to indicate that the novel homozygous variant c.T1641A (p.Y547*) in the CHDR1 gene might be the disease‐causing mutation for retinal dystrophy in our patient, extending its mutation spectrums. These findings further the understanding of the molecular pathogenesis of this disease and provide new insights for diagnosis as well as new implications for genetic counselling.